Association Between Reduced Risk of Intracerebral Hemorrhage and Pelvic Inflammatory Disease. Issue 5 (February 2016) - Tseng, Chun-Hung; Muo, Chih-Hsin; Lin, Ming-Chia; Kao, Chia-Hung
Abstract : Abstract: This study examines whether pelvic inflammatory disease (PID) facilitates the development of intracerebral hemorrhage (ICH). By using outpatient claims data from the National Health Insurance Research Database (NHIRD) of Taiwan, we included the data of 25, 508 patients who were newly diagnosed with PID between 1999 and 2004, and also from the Taiwan NHIRD, we randomly selected 102, 032 women without PID, who were frequency-matched by age and entry-year and with 4 times the number of the PID patients, as the control cohort. We measured ICH risks associated with PID and comorbidities, including hyperlipidemia, diabetes, hypertension, ischemic heart disease, and atrial fibrillation, by the end of 2011. In comparison with the controls, the ICH hazard was less in the PID group with an adjusted hazard ratio (aHR) of 0.67 (95% confidence interval [CI]:0.50–0.90), which was noted by calculation with the Cox proportional regression model. The ICH risk in the PID patients reduced progressively with the advance of age, with aHRs of 0.75 (95% CI:0.41–1.39) and 0.50 (95% CI:0.29–0.88), respectively, in the age <35-year and age ≥50-year groups. ICH risk lowered gradually with the progress of PID severity, from mild PID with an aHR of 0.72 (95% CI:0.53–0.98) to severe PID with that of 0.30 (95% CI:0.10–0.92). PID patients without any comorbidites had lower ICH risk (aHR = 0.63, 95% CI:0.42–0.94) than the controls without any comorbidites did. Our findings revealed that PID is associated with reduced ICH development, especially for older patients.